2013
DOI: 10.1016/j.proenv.2013.04.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallization Time on Behaviors of Glass-ceramic Produced from Sludge Incineration Ash

Abstract: Incineration has become a significant treatment method for municipal sewage sludge because of the rising difficulty to find suitable sites for traditional landfill. However, a large amount of sludge incineration ash containing high levels of heavy metals is remained. In order to achieve resource utilization, glass-ceramics have been produced using sludge incineration ash. The optimum heat treatment was identified as T n = 837 o C for 1.0 h and T c = 977 o C for 2.0 h, respectively. The major crystalline phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The amorphous content of SSA ranged from 35-75%, which suggests that the material is somewhat reactive and, when ground sufficiently fine, may have potential as a cement component. Table 1 has been prepared to provide analysis of the extensively reported toxic and non-toxic element concentrations of SSA [2,4,12,13,17,28,30,32,34,35,42,44,45,49,55,56,58,[70][71][72][73][74]76,82,83,85,87,97,[100][101][102][103][104]107,108,.…”
Section: Mineralogymentioning
confidence: 99%
“…The amorphous content of SSA ranged from 35-75%, which suggests that the material is somewhat reactive and, when ground sufficiently fine, may have potential as a cement component. Table 1 has been prepared to provide analysis of the extensively reported toxic and non-toxic element concentrations of SSA [2,4,12,13,17,28,30,32,34,35,42,44,45,49,55,56,58,[70][71][72][73][74]76,82,83,85,87,97,[100][101][102][103][104]107,108,.…”
Section: Mineralogymentioning
confidence: 99%
“…It was observed that lower porosity contributed to the higher density value [9], therefore, at 700 °C, the density of 40 wt.% SBE was 2.15 g/cm, while the density of 45 wt.% and 55 wt.% of SBE decreased to 1.78 and 1.82 g/cm 3 respectively. However, on 55 wt.% of SBE loading at 700 °C and 750 °C, the densities obtained were not consistent with the porosities and it was also observed that the percentage of porosities and water absorption of the 850 °C samples were slightly increased.…”
Section: Resultsmentioning
confidence: 97%
“…Rice husk ash, produced in biomass power plants that use rice husk as fuel, has been used as a silica precursor since it contains around 85–90% of amorphous or crystalline silica depending on the combustion conditions . Sewage sludge fly ash, paper sludge ash, oil‐shale ash or meat and bone meal ashes feature a lower content of silica, but they contain significant amounts of P 2 O 5 (another glass forming oxide) and Al 2 O 3 (‘intermediate’ glass forming oxide, when combined with alkali or alkaline earth oxides).…”
Section: Inorganic Waste As Raw Materials For Glass‐based Productsmentioning
confidence: 99%